2022
DOI: 10.3390/agronomy12030732
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Five Highbush Blueberry Cultivars to In Vitro Induced Drought Stress by Polyethylene Glycol

Abstract: Stress caused by drought is an important factor that affects the growth and development of highbush blueberry plants. In vitro screening for drought stress tolerance is of major importance in identifying cultivars that have optimal stress tolerance and productivity. The aim of this study was to evaluate the responses of five in vitro-grown highbush blueberry cultivars (Bluecrop, Brigitta Blue, Duke, Goldtraube and Hortblue Petite) under drought stress. Five concentrations of polyethylene glycol (PEG 6000), 0 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Regarding shoot lengths (Figure 2b), they recorded maximum values at Hortblue Petite on solid culture medium supplemented with 0.5 mg/L Z (3.40 ± 0.20 cm), while Duke had the longest shoots in the TIS in the culture medium supplemented with 5 mg/L 2iP (3.07 ± 0.28 cm), in agreement with our previously reported results [34,46,51].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding shoot lengths (Figure 2b), they recorded maximum values at Hortblue Petite on solid culture medium supplemented with 0.5 mg/L Z (3.40 ± 0.20 cm), while Duke had the longest shoots in the TIS in the culture medium supplemented with 5 mg/L 2iP (3.07 ± 0.28 cm), in agreement with our previously reported results [34,46,51].…”
Section: Resultssupporting
confidence: 91%
“…In solid media, Hortblue Petite had again the highest PR (7.94 ± 0.25) in the medium supplemented with 1 mg/L Z while Duke presented a PR of just 2.98 ± 0.25 (Figure 2a). Similar results were obtained in our previous studies where the Duke variety had the lowest proliferation rate (2.11 ± 0.15) compared to Hortblue Petite (8.50 ± 0.51) on agar gelled with WPM culture medium and supplemented with 1 mg/L Z [51]. Another study showed [44] that Duke cultivar cultured on Anderson (1980) culture medium supplemented with 0.5 mg/L Z or 2iP generated a similar number of shoots/explant, their numbers ranging from 2 to 4.…”
Section: Resultssupporting
confidence: 91%
“…Blueberry is especially prone to adverse effects from drought events ( Erb, 1993 ; Améglio et al., 2000 ; Molnar et al., 2022 ) ( Figure 1 ). Limited drought tolerance of blueberries is a byproduct of their superficial root system, with most blueberries growing roots less than 40 cm deep ( Molnar et al., 2022 ) ( Figure 1 ).…”
Section: Drought Stress Presents a Major Threat To Global Blueberry P...mentioning
confidence: 99%
“…Blueberry is especially prone to adverse effects from drought events ( Erb, 1993 ; Améglio et al., 2000 ; Molnar et al., 2022 ) ( Figure 1 ). Limited drought tolerance of blueberries is a byproduct of their superficial root system, with most blueberries growing roots less than 40 cm deep ( Molnar et al., 2022 ) ( Figure 1 ). Additionally, blueberries lack root hairs, which reduces their absorptive root surface by 90% compared to root systems with root hairs ( Eck, 1966 ; McElrone et al., 2013 ).…”
Section: Drought Stress Presents a Major Threat To Global Blueberry P...mentioning
confidence: 99%
See 1 more Smart Citation